Complementary mechanochemical and biphasic approaches for the synthesis of organic thiocyanates using hexacyanoferrates as non-toxic cyanide sources. Issue 3 (23rd December 2022) - Grundke, Caroline; Groß, Jonathan; Vierengel, Nina; Sirleaf, Jason; Schmitz, Matthias; Krieger, Leonie; Opatz, Till
Abstract : Herein, we describe two complementary approaches towards various organic thiocyanates that are affordable, reliable and follow the principles of sustainable chemistry, starting from commercially available thiols or disulfides. Abstract : Herein, we describe two complementary approaches towards various organic thiocyanates that are affordable, reliable and follow the principles of sustainable chemistry, starting from commercially available thiols or disulfides. Additionally, the application of this mild method to the first total synthesis of psammaplin B is demonstrated. Non-toxic and inexpensive ferricyanide is used as the cyanide source, which can be activated either in a mechanochemical, solvent-free approach, or in a biphasic solvent system allowing easier work-up. A total of 27 examples is demonstrated, with up to quantitative yields.